A novel Ffu fusion system for secretory expression of heterologous proteins in Escherichia coli - Cheng Cheng; Shanshan Wu; Lupeng Cui; Yulu Wu; Tianyue Jiang; Bingfang He (Microbial Cell Factories, 2017)
Abstract Background The high level of excretion and rapid folding ability of β-fructofuranosidase (β-FFase) in Escherichia coli has suggested that β-FFase from Arthrobacter arilaitensis NJEM01 can be developed as a fusion partner. Methods Based on the modified Wilkinson and Harrison algorithm and the preliminary verification of the solubility-enhancing ability of β-FFase truncations, three β-FFase truncations (i.e., Ffu209, Ffu217, and Ffu312) with a native signal peptide were selected as novel Ffu fusion tags. Four difficult-to-express protein models; i.e., CARDS TX, VEGFR-2, RVs and Omp85 were used in the assessment of Ffu fusion tags. Results The expression levels and solubility of each protein were markedly enhanced by the Ffu fusion system. Each protein had a favorable Ffu tag. The Ffu fusion tags performed preferably when compared with the well-known fusion tags MBP and NusA. Strikingly, it was confirmed that Ffu fusion proteins were secreted into the periplasm by the periplasmic analysis and N-amino acid sequence analysis. Further, efficient excretion of HV3 with defined anti-thrombin activity was obtained when it was fused with the Ffu312 tag. Moreover, HV3 remained soluble and demonstrated notable anti-thrombin activity after the removal of the Ffu312 tag by enterokinase. Conclusions Observations from this work not only complements fusion technologies, but also develops a novel and effective secretory system to solve key issues that include inclusion bodies and degradation when expressing heterologous proteins in E. coli, especially for proteins that require disulfide bond formation, eukaryotic-secreted proteins, and membrane-associated proteins.